Pengaruh Metode Bermain dan Bercerita Terhadap Perkembangan Bahasa Anak Di TK Dian Harapan Makkio Baji Takalar - Roihanatus Salsabila; Putri, Adelia; Musfira, Musfira; Martuty, Arie (ISOLEK: Jurnal Pendidikan, Pengajaran, Bahasa, dan Sastra, 2026)
Early childhood language development is a crucial aspect of holistic growth and development, especially in Dian Harapan Makkio Baji Kindergarten in Takalar, located in an area with a language delay rate of 12–14%. This study aims to examine the effect of play and storytelling methods on the expressive language skills of children aged 5–6 years, analyze development before and after intervention, and assess the effectiveness of the integrated application of both methods. Using a Quasi-Experimental design with 14 subjects divided into experimental and control groups, the study was conducted over six weeks with a Likert-scale pretest and posttest. The results showed a significant increase in the experimental group, with an average score of 67.57 to 86.43, while the control group only increased from 65.29 to 68.43. The Wilcoxon test confirmed a significant effect (p = 0.018) of the play and storytelling method on language development, compared to the insignificant change in the control group (p = 0.310). Thus, this method is proven to be effective in improving the quality of children's language development objectively and measurably.